Decision Making in the Wait-and-Scan Approach for Vestibular Schwannomas: Is There a Price to Pay in Terms of Hearing, Facial Nerve, and Overall Outcomes?. Issue 5 (21st December 2017) - Prasad, Sampath Chandra; Patnaik, Uma; Grinblat, Golda; Giannuzzi, Annalisa; Piccirillo, Enrico; Taibah, Abdelkader; Sanna, Mario
Abstract: BACKGROUND: The wait-and-scan modality has emerged as an important strategy in the management of vestibular schwannoma (VS) as it has been demonstrated that many tumors grow slowly or do not show any growth over long periods. OBJECTIVE: To analyze long-term outcomes of wait-and-scan in the treatment of patients with VS, discuss the factors contributing to the decision making, determine the inherent risks of the policy, and compare our results with literature. METHODS: In total, 576 patients with sporadic unilateral VS who were managed with wait-and-scan were reviewed retrospectively. Of these, a subset of 154 patients with 5-yr follow-up was separately analyzed. The tumor characteristics including patterns of growth, rate of growth, hearing outcomes, and likely factors affecting the above parameters were analyzed. RESULTS: The mean period of follow-up was 36.9 ± 30.2 mo. The mean age was 59.2 ± 11.6 yr. Thirteen different patterns of tumor growth were observed. Eighty-four (54.5%) of 154 tumors with 5-yr follow-up showed no growth throughout 5 yr. Fifty-six (36.4%) tumors showed mixed growth rates. Only 57 (37%) patients had serviceable hearing at the start of follow-up, but 32 (56.1%) maintained it at the end of follow-up. One hundred fifty (26%) of the 576 patients who failed wait-and-scan had to be taken up for surgery. CONCLUSION: While there may be no price to pay in wait-and-scan as far as hearing is concerned, this may not be the case for facial nerve outcomes, wherein the results may be better if the patients are taken earlier for surgery.